2021
DOI: 10.3390/su132212900
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Fear of COVID-19 on Purchase Behavior of Dietary Supplements: Integration of the Theory of Planned Behavior and the Protection Motivation Theory

Abstract: This study aimed at assessing the impacts of the fear of COVID-19 on consumer buying behavior toward dietary supplements. This investigation was a cross-sectional study in which literate adults regardless of gender over the age of 20 were recruited from three pharmacies in three different districts of Wuhan City, China. A total of 598 questionnaires were analyzed after excluding 10 with incomplete information. The current study demonstrated that attitudes, subjective norms, and perceived behavioral control had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 86 publications
(123 reference statements)
3
20
0
Order By: Relevance
“…At present, the C19P-S has been developed and adapted to multiple languages and cultures, including Turkish, English, Russian, Korean, and Japanese. However, a study with a Chinese population as subjects did not report the results of the reliability and validity tests of the COVID-19 Phobia Scale” [ 16 ]. They only reported the psychological and social dimensions when they applied the “COVID-19 Phobia Scale” to the Chinese samples.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the C19P-S has been developed and adapted to multiple languages and cultures, including Turkish, English, Russian, Korean, and Japanese. However, a study with a Chinese population as subjects did not report the results of the reliability and validity tests of the COVID-19 Phobia Scale” [ 16 ]. They only reported the psychological and social dimensions when they applied the “COVID-19 Phobia Scale” to the Chinese samples.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that individuals with four serious chronic diseases, including cancer, Parkinson's disease, heart disease, and diabetes, had higher scores in avoidance behaviors, anxiety, and depression (20). Another study showed that fear of COVID -19 had a positive influence on people's intention to buy supplements (21).…”
Section: Discussionmentioning
confidence: 99%
“…These studies also indicated that people tend to comply with expectations and restrictions in risky circumstances. Roberts and David (2021) identified that fear of covid-19 can cause increased self-efficacy as well as perceived behavioral control, with the emotional response influencing self-protective behavior (Liu et al, 2021). During the covid-19 pandemic, the perceived threat is positively correlated with the global adoption of preventive measures, resulting in elevated self-protection against the imminent threat (Itani & Hollebeek, 2021).…”
Section: Increase Protection To Maintain Operations (Topic 2)mentioning
confidence: 99%
“…Within the protection measures that take into account a comprehensive approach to reduce the transmission of covid-19 both inside and outside the facilities, that is, not only focusing on consumers but also on the staff working in organizations, we can highlight: vaccination of employees, ensuring that social distancing is practiced, ensuring that masks are Marketing used appropriately, periodically evaluating employees for covid-19, promoting frequent hand washing, cleaning surfaces exposed to different people, and ensure adequate ventilation (Trm ic ´ et al, 2021). Liu et al (2021) suggested that protective motivation theory (pmt) is often used when an individual's self-protective behaviors arise through fear, such as the fear many people have experienced contracting covid-19. In the context of the pandemic we are experiencing, pmt can help understand how consumers perceive threats and how their reaction, when faced with them, impacts their behavior.…”
Section: Increase Protection To Maintain Operations (Topic 2)mentioning
confidence: 99%
See 1 more Smart Citation